STRATEGI PENCEGAHAN DALAM TAHAP REHABILITASI DI RUMAH PERLINDUNGAN TRAUMA CENTER (RPTC) TERHADAP ANAK YANG TERLIBAT PRAKTEK PROSTITUSI - Usmita , Fakhri; Saleh, Ramdan (Sisi Lain Realita, 2024)
The aim of this research was to see how the prevention strategies of RPTC (Trauma Center Protection House) in handling with cases of child prostitution in the Riau Province Social Service and anything related to RPTC social workers in cases of prostitution against children in the Riau Province Social Service. This research method is a qualitative research method using the case study method. The writer did this research with the workers of the Riau Province Social Service RPTC. Key informants and information in this study were the Head of Social Rehabilitation and Social Worker Division of RPTC Social Service of Riau Province. Techniques of studying data in this research are interviews, observation and documentation. The data analysis technique in this research uses descriptive analysis of qualitative data, namely trying to analyze by describing, explaining and explaining clearly, accurately and as it is in accordance with what is the object of the research. Based on interviews and research results has known that the pattern of handling cases of RPTC workers in cases of child prostitution has been maximally implemented and is in accordance with the stipulated SOP, the victim is investigated first after that is given protection in the form of mental and psychological health, for trauma treatment offered by the victim.